2008
DOI: 10.1007/s00062-008-8028-2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Spinal Cord Herniation: MR Imaging and Clinical Features in Six Cases

Abstract: Background and Purpose: Spontaneous spinal cord herniation (SSCH) is a rare but important differential diagnosis of spinal cord disorder. The aim of this study was to evaluate the topography and lesion pattern in six patients with SSCH by magnetic resonance imaging (MRI) and their correlation with clinical symptoms. Material and Methods: MRI was evaluated according to intramedullary hyperintense signal changes, alterations of the posterior vertebra and dorsal subarachnoid space at the level of the herniation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The most frequent misinterpretation is as a dorsal arachnoid cyst[145678101112131415161718192021232425] previously reported as a false diagnosis in around 45% of cases,[7980] but it has been reported that an associated dorsal arachnoid cyst is potentially present in 20-25% of patients with ISCH. [7980] Other misdiagnoses include thoracic disc herniation,[1213] transverse myelitis,[914] arachnoiditis,[4] intradural mass,[9] and extradural compressive lesion. [1] Misdiagnosis has been reported to result in erroneous surgery, with lack of clinical improvement or progressive neurological symptoms resulting in a second operation to address the spinal cord herniation.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent misinterpretation is as a dorsal arachnoid cyst[145678101112131415161718192021232425] previously reported as a false diagnosis in around 45% of cases,[7980] but it has been reported that an associated dorsal arachnoid cyst is potentially present in 20-25% of patients with ISCH. [7980] Other misdiagnoses include thoracic disc herniation,[1213] transverse myelitis,[914] arachnoiditis,[4] intradural mass,[9] and extradural compressive lesion. [1] Misdiagnosis has been reported to result in erroneous surgery, with lack of clinical improvement or progressive neurological symptoms resulting in a second operation to address the spinal cord herniation.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis is supported by findings described on radiological examination: nuclear trail ( 78 ), clefts in the vertebral body at the level of MRI pathology ( 1 , 96 ), and a cavity in the vertebral body at the level of pathology ( 29 ). A nuclear trail or clefts indicates that the somites did not properly fuse.…”
Section: Discussionmentioning
confidence: 61%
“…Idiopathic spinal cord herniation has an unknown cause which is unrelated to trauma or a previous operation. Pressure erosion, thoracic disc extrusion, congenital disorder (preexisting ventral meningocele), duplication of the ventral duramater, congenital extradural arachnoid cyst, inflammatory process and congenital abnormal adhesions of the spinal cord to the anterior dura are possible underlying causes that have been postulated to explain the occurrence of this dural defect 1,10 .…”
Section: Discussionmentioning
confidence: 99%
“…1,2). Sagittal T2-weighted MR image showed a focal anterior kink of the spinal cord at the T5-T6 level.…”
mentioning
confidence: 99%